2021
DOI: 10.1002/hec.4244
|View full text |Cite
|
Sign up to set email alerts
|

Cost sharing and the demand for health services in a regulated market

Abstract: This paper measures consumer responsiveness to cost sharing in healthcare using a regression discontinuity design. I use a novel and detailed claims-level dataset from the Colombian healthcare market, where the government exogenously determines a tier system for coinsurance rates and copays based on the enrollee's monthly income. I find that patients exposed to higher coinsurance rates demand fewer services relative to patients facing lower cost sharing. This reduction holds for both discretionary and preventi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 35 publications
1
5
0
Order By: Relevance
“…The results of the study showed that “demand side cost sharing“ or “consumer cost sharing” were the main strategies used for controlling consumer moral hazard as addressed by 56 studies [ 5 , 6 , 9 , 10 , 13 , 15 , 18 – 25 , 30 71 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The results of the study showed that “demand side cost sharing“ or “consumer cost sharing” were the main strategies used for controlling consumer moral hazard as addressed by 56 studies [ 5 , 6 , 9 , 10 , 13 , 15 , 18 – 25 , 30 71 ].…”
Section: Resultsmentioning
confidence: 99%
“…The studies included in this theme investigated consequences such as the utilization of health services, health costs, health related behavior, the choice of insurance plan, and the opinion and acceptance of consumers using quantitative, qualitative, review, and theoretical approaches (model-based), the results of quantitative studies are reported in narrative form as follows: modest to high reduction in health services and medications utilization [ 9 , 20 , 21 , 23 , 33 , 38 , 44 , 45 , 47 , 49 , 51 , 55 , 56 , 64 , 69 , 71 ], reduction in health cost [ 21 , 39 , 41 , 42 , 44 , 53 , 65 , 68 ], low or no significant effect on health services utilization [ 6 , 34 , 35 , 40 , 62 , 63 , 65 ], low or no significant effect on health costs [ 5 ], increasing cost contaminate incentive (CCI) [ 57 ], significant correlation with higher preventive behavior [ 13 , 50 ] modest efficiency gain [ 18 ], increasing medication adherence [ 48 ], increasing demand for low price drug [ 61 ], optimal insurance [ 54 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Economic theory suggests that cost sharing would reduce patients' demand for health services by increasing prices paid by patients at the time of health services utilization ( 7 , 8 ). The true effects of cost sharing on demand for various health services, however, vary within health insurance systems ( 9 , 10 ). For instance, cost-sharing tactics for prescription drugs might not be generalizable to effective cost sharing for doctors' outpatient or inpatient services.…”
Section: Introductionmentioning
confidence: 99%